Association between county-level coal-fired power plant pollution and racial disparities in preterm births from 2000 to 2018. (2nd March 2021) - Daouda, Misbath; Henneman, Lucas; Kioumourtzoglou, Marianthi-Anna; Gemmill, Alison; Zigler, Corwin; Casey, Joan A
Abstract: Coal has historically been a primary energy source in the United States (U.S.). The byproducts of coal combustion, such as fine particulate matter (PM2.5 ), have increasingly been associated with adverse birth outcomes. The goal of this study was to leverage the current progressive transition away from coal in the U.S. to assess whether coal PM2.5 is associated with preterm birth (PTB) rates and whether this association differs by maternal Black/White race/ethnicity. Using a novel dispersion modeling approach, we estimated PM2.5 pollution from coal-fired power plants nationwide at the county-level during the study period (2000–2018). We also obtained county-level PTB rates for non-Hispanic White and non-Hispanic Black mothers. We used a generalized additive mixed model to estimate the relationship between coal PM2.5 and PTB rates, overall and stratified by maternal race. We included a natural spline to allow for non-linearity in the concentration–response curve. We observed a positive non-linear relationship between coal PM2.5 and PTB rate, which plateaued at higher levels of pollution. We also observed differential associations by maternal race; the association was stronger for White women, especially at higher levels of coal PM2.5 (>2.0 μ g m −3 ). Our findings suggest that the transition away from coal may reduce PTB rates in the U.S.